2014
DOI: 10.1186/1471-2407-14-661
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rs2802292 SNP identifies FOXO3Aas a modifier locus predicting cancer risk in patients with PJS and PHTS hamartomatous polyposis syndromes

Abstract: BackgroundHamartomatous polyposis syndromes (HPS) are inherited conditions associated with high cancer risk. They include the Peutz-Jeghers and the PTEN hamartoma tumor syndromes, which are caused by mutations in the LKB1 and PTEN genes, respectively. Estimation of cancer risk is crucial in order to optimize surveillance, but no prognostic markers are currently available for these conditions. Our study relies on a ‘signal transduction’ hypothesis based on the crosstalk between LKB1/AMPK and PI3K/PTEN/Akt signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Importantly, previous reports failed to find an association between FOXO3 -coding variants and longevity [108]. Conversely, among non-coding genetic variants, the G-allele of the rs2802292 SNP, located in FOXO3 intron 2, has been reported to be strongly associated with longevity in different human populations [109,110]. A recent work showed that the 90-bp sequence around rs2802292 has an enhancer function.…”
Section: Architecture Of Foxo3a Domains and Its Nuclear Functionsmentioning
confidence: 99%
“…Importantly, previous reports failed to find an association between FOXO3 -coding variants and longevity [108]. Conversely, among non-coding genetic variants, the G-allele of the rs2802292 SNP, located in FOXO3 intron 2, has been reported to be strongly associated with longevity in different human populations [109,110]. A recent work showed that the 90-bp sequence around rs2802292 has an enhancer function.…”
Section: Architecture Of Foxo3a Domains and Its Nuclear Functionsmentioning
confidence: 99%
“…In a recent study on patients with hamartomatous polyposis syndromes (HPS), an inverse correlation between the rs2802292 G-allele and cancer risk has been described. These syndromes are characterized by mutations in STK11 (Peutz-Jeghers syndrome, PJS) or PTEN (PTEN hamartoma tumor syndrome, PHTS) [71], which encode for FOXO3 upstream regulators [29]. Indeed, longevity-associated SNPs that do not act as protein-coding variants may reside in regulatory regions responsible for the activation of gene expression [72].…”
Section: Lessons From Foxo3 Snpsmentioning
confidence: 99%
“…Indeed, longevity-associated SNPs that do not act as protein-coding variants may reside in regulatory regions responsible for the activation of gene expression [72]. For example, it was recently shown that the intronic rs2802292 G-allele is associated with increased FOXO3 basal expression [71,73] and that homozygosity for the G-allele correlates with lower frequency of age-related diseases in centenarians [35]. These data suggest that FOXO3 intron 2, and in particular the rs2802292 SNP, may act as a regulatory region.…”
Section: Lessons From Foxo3 Snpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous single nucleotide polymorphisms (SNPs) located in intronic regions of the gene have been shown to be associated with longevity in different human populations [56,57,58,59,60]. Notably, in humans the rs2802292 SNP G-allele at FOXO3a locus correlates with reduced frequency of age-related diseases in centenarians [61,62] and is associated with mortality risk reduction for coronary heart disease [63,64]. Moreover, it has been found to have enhancer functions, creating a binding site for HSF1 in response to stress stimuli [62].…”
Section: The Foxo Family and Foxo3amentioning
confidence: 99%